Bring me a rock! - Miyares, Daniel (Simon & Schuster Books for Young Readers, 2016)
"A tiny insect king demands a rock with which to build his throne"...
Keywords: Kings, queens, rulers, etc; Ants; Humorous stories; Bilderbuch; Kinderbuch